Paleo‐thermal constraints on the origin of native diagenetic sulfur in the Messinian evaporites: The Northern Apennines foreland basin case study (Italy). (15th May 2021) - Rossi, Francesco Paolo; Schito, Andrea; Manzi, Vinicio; Roveri, Marco; Corrado, Sveva; Lugli, Stefano; Reghizzi, Matteo
Abstract: Recent studies on the genesis of sedimentary native sulfur deposits indicate diagenetic mid‐low temperature Bacterial Sulfate Reduction (BSR) as the main process, involving organic compounds (kerogen/hydrocarbons), bacterial colonies and gypsiferous rocks. In the peri‐Mediterranean area (Southern Spain, Sicily, Northern Apennines, Israel), the main sulfur accumulations are always associated with late Miocene sulfates and organic‐rich successions encompassing the Messinian salinity crisis (MSC). In particular, the Messinian successions of the Apennine‐Adriatic foreland basin system, due to a large amount of high‐resolution stratigraphic data, represent a perfect case study for understanding the diagenetic conditions controlling the development of the BSR process during sedimentary basin evolution. In this work, thermal models performed in three sub‐basins in a sector of the Northern Apennines comprised of the Sillaro and Marecchia rivers (Italy), calibrated by means of organic and inorganic geothermometers, indicate a general thermal immaturity of the studied successions attained as a result of a constant heat flow similar to the present day one (ca. 40 mW/m 2 ) since Late Tortonian and lithostatic loads between 615 and 1, 710 m depending on different sub‐basins. These results suggest that the MSC deposits experienced maximum temperatures between about 39°C and 65°C. Temperatures derived from thermal models have been used to constraint occurrence of the diagenetic BSR associated with evaporitic deposits providing thermal constraints in sulfur genesis as well as new useful thermal‐constraints for basin analysis studies. Abstract : The manuscript presents the first attempt to define the diagenetic conditions (burial and related paleo‐temperatures) for sulfur formation in relationship with the deposits generated by the Messinian salinit crisis. ​